Personalisation and the Libertarian Roots of Populism - Eran Fisher (tripleC: Communication, Capitalism & Critique)
This article seeks to lay bare the connection between personalisation in digital media and populism. Underpinning both the technology and the political ideology is a shared promise. They offer similar answers to the epistemological and methodological questions: “what is the true will of (the) people?”, and “how to tap into it?”. Both personalisation and populism assume that modern, reflexive, critical subjectivity has veiled this authentic will, and both offer alternative routes to salvage it and bring it to the fore of individual and political life. Theoretically, I follow the seminal work of Shapin and Schaffer, Leviathan and the Air-Pump, highlighting the link between two seemingly autonomous discourses: technical/scientific, on the other hand, and political, in the other hand. The justification for one, they show, resonates the other. Empirically, I focus on the discourse of personalisation in the cultural field, and show how it promises to democratise Culture (capital C) – as a unified, hierarchical, to-down, elitist, and shared social field – by giving users the technological means to tap into their real wants and desires. The promise encapsulated in personalisation – a technological assemblage of digital platforms, big data, and algorithms – echoes the anti-elitist sentiment of populist ideology.